Genetic evidence does not support an etruscan origin in Anatolia. Issue 1 (30th July 2013) - Tassi, Francesca; Ghirotto, Silvia; Caramelli, David; Barbujani, Guido
ABSTRACT The debate on the origins of Etruscans, documented in central Italy between the eighth century BC and the first century AD, dates back to antiquity. Herodotus described them as a group of immigrants from Lydia, in Western Anatolia, whereas for Dionysius of Halicarnassus they were an indigenous population. Dionysius' view is shared by most modern archeologists, but the observation of similarities between the (modern) mitochondrial DNAs (mtDNAs) of Turks and Tuscans was interpreted as supporting an Anatolian origin of the Etruscans. However, ancient DNA evidence shows that only some isolates, and not the bulk of the modern Tuscan population, are genetically related to the Etruscans. In this study, we tested alternative models of Etruscan origins by Approximate Bayesian Computation methods, comparing levels of genetic diversity in the mtDNAs of modern and ancient populations with those obtained by millions of computer simulations. The results show that the observed genetic similarities between modern Tuscans and Anatolians cannot be attributed to an immigration wave from the East leading to the onset of the Etruscan culture in Italy. Genetic links between Tuscany and Anatolia do exist, but date back to a remote stage of prehistory, possibly but not necessarily to the spread of farmers during the Neolithic period. Am J Phys Anthropol 152:11–18, 2013. © 2013 Wiley Periodicals, Inc.